Two-colour X-gamma ray inverse Compton back-scattering source. (28th December 2017) - Drebot, I.; Petrillo, V.; Serafini, L.
Abstract: We present a simple and new scheme for producing two-colour Thomson/Compton radiation with the possibility of controlling separately the polarization of the two different colours, based on the interaction of one single electron beam with two light pulses that can come from the same laser setup or from two different lasers and that collide with the electrons at different angle. One of the most interesting cases for medical applications is to provide two X-ray pulses across the iodine K -edge at 33.2 keV. The iodine is used as contrast medium in various imaging techniques and the availability of two spectral lines accross the K -edge allows one to produce subtraction images with a great increase in accuracy.